Determinants of Kidney Function and Accuracy of Kidney Microcysts Detection in Patients Treated With Lithium Salts for Bipolar Disorder - Tabibzadeh, Nahid; Faucon, Anne-Laure; Vidal-Petiot, Emmanuelle; Serrano, Fidéline; Males, Lisa; Fernandez, Pedro; Khalil, Antoine; Rouzet, François; Tardivon, Coralie; Mazer, Nicolas; Dubertret, Caroline; Delavest, Marine; et al. (Frontiers in Pharmacology, 2022)
Objectives. Early kidney damage during lithium treatment in bipolar disorder is still hypothetical. We aimed at identifying the determinants of a decreased measured glomerular filtration rate (mGFR) and the accuracy of kidney MRI imaging in its detection. Methods. In this cross-sectional cohort study, 217 consecutive lithium-treated patients underwent mGFR and kidney MRI with half-Fourier turbo spin-echo and Single-shot with long echo time sequences. Results. Median age was 51 [27-62] years, and median lithium treatment duration was 5 [2-14] years. 52% of patients had a stage 2 CKD. In multivariable analysis, the determinants of a lower mGFR were a longer lithium treatment duration (β -0.8 [-1; -0.6] ml/min/1.73m² GFR decrease for each year of treatment), a higher age (β -0.4 [-0.6; -0.3] ml/min/1.73m² for each year of age, p<0.001), albuminuria (β -3.97 [-6.6;-1.3], p=0.003), hypertension(β -6.85 [-12.6;-1.1], p=0.02) and hypothyroidism (β -7.1 [-11.7;-2.5], p=0.003). Serum lithium concentration was not associated with mGFR. Renal MRI displayed renal microcyst(s) in 51% of patients, detected as early as one year after lithium treatment initiation. mGFR and lithium treatment duration were strongly correlated in patients with microcyst(s) (r=-0.64, p<0.001), but not in patients with no microcysts (r=-0.24, p=0.09). The presence of microcysts was associated with the detection of an mGFR <45 ml/min/1.73m2 (AUC 0.893, p<0.001, sensitivity 80%, specificity 81% for a cut-off value of 5 microcysts). Conclusions. Lithium treatment duration and hypothyroidism strongly impacted mGFR independently of age, especially in patients with microcysts. MRI might help detect early lithium-induced kidney damage and inform preventive strategies.